THE PHENOMENON OF "COHESION" FROM THE POSITION OF SOCIOLOGICAL KNOWLEDGE - Lubysheva, L.I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to consider the phenomenon of "cohesion" in the aspect of a comparative analysis of its socio-psychological characteristics. Results and conclusions. The author notes that in psychological science the phenomenon of cohesion is considered in the context of building an internal positive climate of the group. In contrast to the psychological understanding of the phenomenon of cohesion, sociological science explains it from the standpoint of a social space in which the group is only a structure that performs its functions in accordance with the target orientation of the organization in which it functions. For a broad understanding and consideration of the problems of the “cohesion” phenomenon, an effective way to study them is specific sociological research based on the survey method, the main advantage of which lies in the possibility of knowing various areas of social practice. The use of sociological tools in the study of various aspects of "cohesion" implements the interdisciplinarity of methodological approaches in the study of this scientific category.